2012
DOI: 10.1002/sim.5682
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of covariate effects in generalized linear mixed models with a misspecified distribution of random intercepts and slopes

Abstract: Generalized linear mixed models with random intercepts and slopes provide useful analyses of clustered and longitudinal data and typically require the specification of the distribution of the random effects. Previous work for models with only random intercepts has shown that misspecifying the shape of this distribution may bias estimates of the intercept, but typically leads to little bias in estimates of covariate effects. Very few papers have examined the effects of misspecifying the joint distribution of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 16 publications
5
61
0
1
Order By: Relevance
“…The ShapiroWilk test indicates that the normality assumption of the random lemmaspecific intercepts is slightly violated (W = 0.98894, p-value = 0.0189). However, the misspecification of the distribution of random effects has little effect on estimates of covariate effects (McCulloch and Neuhaus 2011;Neuhaus et al 2013). It is therefore concluded that the slight violation of the normality assumption of the random lemma-specific intercepts does not pose problems for interpreting the main effects of the model.…”
Section: Variable Importance In the Corpus-based Mixed-effects Logistmentioning
confidence: 95%
“…The ShapiroWilk test indicates that the normality assumption of the random lemmaspecific intercepts is slightly violated (W = 0.98894, p-value = 0.0189). However, the misspecification of the distribution of random effects has little effect on estimates of covariate effects (McCulloch and Neuhaus 2011;Neuhaus et al 2013). It is therefore concluded that the slight violation of the normality assumption of the random lemma-specific intercepts does not pose problems for interpreting the main effects of the model.…”
Section: Variable Importance In the Corpus-based Mixed-effects Logistmentioning
confidence: 95%
“…Previous research on GLMMs has shown that misspecifying the shape of the random-effects distribution reduces the accuracy of random-effects predictions, but has little effects on the fixed-effects parameter estimates (e.g., Neuhaus, McCulloch, & Boylan, 2013). This indicates that for GLMM trees, misspecification of the shape of the randomeffects distribution will affect random-effects predictions, but will have little effect on the estimated tree.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…Maximum likelihood estimates for fixed effects and variance components obtained under the assumption of Gaussian distributed random effects have been shown to be consistent and asymptotically normally distributed under broad regularity conditions, even when the random effects distribution is misspecified Lesaffre, 1996, 1997;Neuhaus et al, 2013). Although the estimates are consistent, sandwich-type corrections are required to obtain the correct asymp-totic standard errors (Butler and Louis, 1992;Verbeke and Lesaffre, 1997).…”
Section: Impact Of Misspecifying the Random Effects Distributionmentioning
confidence: 98%
“…Heagerty and Kurland 2001;Neuhaus and McCulloch 2006;Huang 2009;Neuhaus and McCulloch 2014), incorrectly assuming independence to the cluster size , and incorrectly specifying the distribution (e.g. Heagerty and Kurland 2001;McCulloch and Neuhaus 2011a;Neuhaus et al 2013). …”
Section: Assumptions and Complexities Of Generalised Linear Mixed Modelsmentioning
confidence: 99%
See 1 more Smart Citation